Is regulation by milestones efficiency enhancing?: An experimental study of environmental protection - Freytag, Andreas; Güth, Werner; Koppel, Hannes; Wangler, Leo (European journal of political economy, 2014)
We analyze the effect of “milestones” on reaching a long-term target, which if missed implies dramatic payoff risks. In our experiment, a cumulative threshold public goods game, milestones are captured by intermediate contribution targets on the way to the final target. Missing the final target leads to a probabilistic total loss for all players, and missing intermediate targets may lead to the same consequences even earlier. The additional intermediate targets feature environmental protection as a process rather than a contest for reaching a final target. The regulating agency is Nature, although political agencies might implement a similar regulation. We test milestone effects by varying the size of milestones in addition to changing the marginal productivity of individual contributions and the payoff risk. Although we observe some milestone effects, additional regulation by milestones on its own does not guarantee that targets are reached.